High performance thin film solar cells on plastic substrates with nanostructure-enhanced flexibility. (April 2016) - Lin, Qingfeng; Lu, Linfeng; Tavakoli, Mohammad Mahdi; Zhang, Chi; Lui, Ga Ching; Chen, Zhuo; Chen, Xiaoyuan; Tang, Lei; Zhang, Daquan; Lin, Yuanjing; Chang, Paichun; Li, Dongdong; et al.
Abstract: Plastic substrates possess conspicuous advantages for flexible thin film solar cell applications due to their superior flexibility and light weight characteristics. However, there are several challenges of using plastic substrates for high performance thin film solar cells since they usually have low melting/softening temperature and high coefficient of thermal expansion (CTE). In this work, we demonstrated a low cost process to achieve regular nanocone arrays on polyimide (PI) substrates which have unique photon management property and excellent mechanical flexibility. To leverage these benefits of the nanocone substrates, flexible amorphous Si solar cells were fabricated on the structures. Intriguingly, it was discovered that properly designed nanocones can significantly improve solar cell device performance via light management. And the fabrication yield of properly designed nanocone solar cells is much higher than that of planar devices. In addition, the nanocone plastic solar cells possess much improved bendability and robustness verified by both experiment and mechanical modeling, showing unique stress release mechanism originated from three-dimensional nanostructure design. This property is of practical significance for flexible electronics not limited to solar cells. Graphical abstract: Highlights: Properly designed nanocones can significantly improve solar cell device performance via light management. The fabrication yield of properly designed nanocone solar cells is much higher than that of planar devices. The nanocone plastic solar cells possess much improved bendability and robustness.